2017
DOI: 10.1080/00380768.2017.1415660
|View full text |Cite
|
Sign up to set email alerts
|

Intercontinental comparison of greenhouse gas emissions from irrigated rice fields under feasible water management practices: Brazil and Japan

Abstract: Flooded rice fields are a significant anthropogenic source of methane (CH 4) and nitrous oxide (N 2 O) from agriculture in Asia, Latin America, and the Caribbean regions. In this work, we comparatively assessed the potential of intermittent irrigation and continuous rice flooding for reducing soil CH 4 and N 2 O emissions, partial global warming potential (pGWP), and its yield-scaled version (YpGWP) in northwestern Japan and southern Brazil. Seasonal CH 4 emissions under continuous flooded soils were slight hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
2
4
0
1
Order By: Relevance
“…4b) crop seasons, respectively. A large contribution of CH 4 in GWP related to N 2 O was observed in several other works (Bayer et al 2015;Camargo et al 2018;Zschornack et al 2018). These results demonstrate the great importance of CH 4 emitted in rice fields and the need to add mitigating measures for the emission of the gas.…”
Section: Partial Global Warming Potential Grain Yield and Pgwp/ysupporting
confidence: 71%
See 1 more Smart Citation
“…4b) crop seasons, respectively. A large contribution of CH 4 in GWP related to N 2 O was observed in several other works (Bayer et al 2015;Camargo et al 2018;Zschornack et al 2018). These results demonstrate the great importance of CH 4 emitted in rice fields and the need to add mitigating measures for the emission of the gas.…”
Section: Partial Global Warming Potential Grain Yield and Pgwp/ysupporting
confidence: 71%
“…These results are similar to those ones observed when Moterle et al (2013) evaluated permanent irrigation application (381.90 kg CH 4 .ha -1 ) and intermittent irrigation (313.5 kg CH 4 .ha -1 ). Studying different water management, Camargo et al (2018) had results that ranged from 237 (two intermittency in the rice cycle) to 623 (permanent irrigation) kg CH 4 .ha -1 , while Zschornack et al (2018) verified variation of CH 4 between 250.9 and 671.5 kg CH 4 .ha -1 . Furthermore, Bayer et al (2015) evaluated seven crop seasons of the rice and found average emission per crop of 367 kg CH 4 .ha -1 .…”
Section: Methane Emissionmentioning
confidence: 99%
“…하지 만, 동일한 논임에도 불구하고 기후, 토양 조건 및 영농방식에 따라 배출되는 온실가스 배출 경향과 그 양이 달라지고 (Ahn et al, 2014;Liu et al, 2019a), 특히, 동아시아의 경우 장마 기후로 인한 CH 4 배출이 더욱 주목받고 있다 (Ito et al, 2022). 그동안 논물 관리에 관한 온실가스 완화 효과 및 쌀 생산량을 개별적으로 조사 및 분석한 연구는 상당부분 진행되어왔다 (Camargo et al, 2018;Bui et al, 2022)…”
Section: Introductionunclassified
“…Some studies suggest that CH 4 fluxes differ among rice varieties [21,22]. Conversely, other studies suggest that CH 4 fluxes remain consistent among different crop varieties subjected to intermittent irrigation, while intermittent irrigation decreases CH 4 fluxes by 65% compared to flooding conditions [23]. Many studies have investigated the effects of fertilizer and water management on GHG emissions from rice fields [21][22][23].…”
Section: Introductionmentioning
confidence: 99%